Analisis pendeketan terapi realitas dalam meningkatkan identitas diri pengguna apk TikTok - Wardania, Siti; Ardani, Tristia Ardi (Maliki Interdisciplinary Journal, 2024)
This research expands the reality therapy approach to improve the self-identity of TikTok users. TikTok, a popular app, has had a major influence on the way users interact and express themselves, with both positive and negative impacts on their self-identity. Self-identity is an important element in an individual's life and can be influenced by social media. Reality therapy is a method that helps individuals face their reality more healthily and responsibly, using the WDEP (Want, Direction & Doing, Evaluation, Planning) approach to encourage positive changes in behavior and self-identity. This research identifies real therapeutic potential in helping TikTok users and other individuals develop healthier self-identities in the complex social media environment.The method applied in this research is a qualitative approach using literature study.